2020
DOI: 10.1002/advs.201903708
|View full text |Cite
|
Sign up to set email alerts
|

High‐Contrast Optical Modulation from Strain‐Induced Nanogaps at 3D Heterogeneous Interfaces

Abstract: The realization of high‐contrast modulation in optically transparent media is of great significance for emerging mechano‐responsive smart windows. However, no study has provided fundamental strategies for maximizing light scattering during mechanical deformations. Here, a new type of 3D nanocomposite film consisting of an ultrathin (≈60 nm) Al2O3 nanoshell inserted between the elastomers in a periodic 3D nanonetwork is proposed. Regardless of the stretching direction, numerous light‐scattering nanogaps (corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 49 publications
1
53
0
Order By: Relevance
“…4G , without compromising the structure’s ability to serve as a robust scaffold. To this end, the great potential of this structure includes mainframes of gate-all-around field-effect transistors ( 10 ), 3D memory ( 42 ), catalysts ( 8 ), and sensors ( 43 , 44 ). Extending the inversely designed dimensions of PnP from 2D to 3D ensures that functional materials defined in arbitrary 3D periodic shapes with nanoscale resolution can be manufactured via a fast, stable, cost-effective, and mass-producible process.…”
Section: Resultsmentioning
confidence: 99%
“…4G , without compromising the structure’s ability to serve as a robust scaffold. To this end, the great potential of this structure includes mainframes of gate-all-around field-effect transistors ( 10 ), 3D memory ( 42 ), catalysts ( 8 ), and sensors ( 43 , 44 ). Extending the inversely designed dimensions of PnP from 2D to 3D ensures that functional materials defined in arbitrary 3D periodic shapes with nanoscale resolution can be manufactured via a fast, stable, cost-effective, and mass-producible process.…”
Section: Resultsmentioning
confidence: 99%
“…Other results for air gaps are produced when the strain is applied on the patterned Al 2 O 3 layer infiltrated with PDMS. 27 The methods mentioned above showed the reduced optical properties as well as complicated processes for large-scale manufacturing. The advantage of the air-gap-embedded polymer film in the present work provides a way to get air gaps for high optical properties by simple processes such as O 2 plasma treatment and liquid polymer coating.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Formally, there were a few reports on the embedding air gaps or air bubbles in substrates or films, as summarized in Table . Jeon et al reported that air hole is produced by anodically bonding glass on the patterned Si 3 N 4 hole array . Koh et al reported that the air void is spontaneously formed when the precursor polyamic acid (PAA)-coated glass is submerged in water .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Through the development of micro-/nanotechnologies, it has been proven that nano-physicochemical properties (including the stretchability and thermoelectric and photocatalytic properties) originating from various classes of 3D nanostructures can be successfully extended to bulk properties through an inch-scale production of the pattern [40,53,65,[83][84][85][86][87]. A wide range of high-value-added applications such as energy storage systems [60,[88][89][90][91][92][93][94], optical films [95], structural materials [96][97][98][99][100], and sensory devices [39,58,[101][102][103] have since become possible to implement through a wafer-scale production. It should be mentioned that the material substitution from a 3D polymeric template into ceramic, metal, and organic functional materials through atomic layer deposition [84-87, 89, 91, 95, 98], electroplating [60,83,88,93], and infiltration [40,53], respectively, can be used to expand the technical functionality during this 3D nanofabrication process.…”
Section: Realization Of Large-area 3d Nanopatternsmentioning
confidence: 99%
“…11(d)). To achieve this, a chemically amplified photoresist such as an SU-8 and NR series (Futurrex) whose curing requires further post-baking steps after light exposure was used to initiate a photoacid-catalyzed reaction which changes the solubility of the exposed photoresist in the developer [53,95]. Briefly, the large-area phase mask was first conformally adhered to the surface of the photoresist and exposed to monochromatic light through the mask.…”
Section: Realization Of Large-area 3d Nanopatternsmentioning
confidence: 99%